2022
DOI: 10.3390/nu14214545
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Nutrient Intake, Eating Habits, and Its Association with Maternal Gestational Weight Gain and Offspring’s Birth Weight in Pregnant Adolescents

Abstract: Pregnant adolescents’ diet and eating habits are inadequate; however, their association with gestational weight gain (GWG) is uncertain. We aimed to analyze whether there is an association between dietary and nutrient intake and eating habits with GWG among pregnant adolescents and their offspring’s birth weight. A longitudinal study was performed with 530 participants. We assessed GWG and applied several tools, such as a food frequency questionnaire and 24-h recall, to obtain dietary and nutrient intake and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…Therefore, it is considered that the majority of pregnant adolescents do not reach the recommended levels of intake for macronutrients and micronutrients. This trend is consistent with findings from other studies, particularly in developing countries [ 7 , 10 , 14 ].…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, it is considered that the majority of pregnant adolescents do not reach the recommended levels of intake for macronutrients and micronutrients. This trend is consistent with findings from other studies, particularly in developing countries [ 7 , 10 , 14 ].…”
Section: Introductionsupporting
confidence: 93%
“…It has been shown that inadequate gestational weight gain in pregnant adolescents is a consequence of poor eating habits, which are very common during adolescence. These habits often include diets rich in carbohydrates and saturated fats, misconceptions about nutrition during pregnancy, delayed or insufficient prenatal care, depression, economic constraints, and inadequate intake of nutritional supplements such as iron and folic acid [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation